CEST MR‐Fingerprinting: Practical considerations and insights for acquisition schedule design and improved reconstruction - Perlman, Or; Herz, Kai; Zaiss, Moritz; Cohen, Ouri; Rosen, Matthew S.; Farrar, Christian T. (Magnetic resonance in medicine, 2020)
Purpose To understand the influence of various acquisition parameters on the ability of CEST MR‐Fingerprinting (MRF) to discriminate different chemical exchange parameters and to provide tools for optimal acquisition schedule design and parameter map reconstruction. Methods Numerical simulations were conducted using a parallel computing implementation of the Bloch‐McConnell equations, examining the effect of TR, TE, flip‐angle, water T1 and T2, saturation‐pulse duration, power, and frequency on the discrimination ability of CEST‐MRF. A modified Euclidean distance matching metric was evaluated and compared to traditional dot product matching. L‐Arginine phantoms of various concentrations and pH were scanned at 4.7T and the results compared to numerical findings. Results Simulations for dot product matching demonstrated that the optimal flip‐angle and saturation times are 30∘ and 1100 ms, respectively. The optimal maximal saturation power was 3.4 μT for concentrated solutes with a slow exchange rate, and 5.2 μT for dilute solutes with medium‐to‐fast exchange rates. Using the Euclidean distance matching metric, much lower maximum saturation powers were required (1.6 and 2.4 μT, respectively), with a slightly longer saturation time (1500 ms) and 90∘ flip‐angle. For both matching metrics, the discrimination ability increased with the repetition time. The experimental results were in agreement with simulations, demonstrating that more than a 50% reduction in scan‐time can be achieved by Euclidean distance‐based matching. Conclusions Optimization of the CEST‐MRF acquisition schedule is critical for obtaining the best exchange parameter accuracy. The use of Euclidean distance‐based matching of signal trajectories simultaneously improved the discrimination ability and reduced the scan time and maximal saturation power required.